Valeriana dacica, a distinctive tetraploid in the Eastern Carpathians - Krahulec, František; Kirschner, Jan; Krahulcová, Anna (Phytotaxa, 2023)
Floras and taxonomic papers covering the region of the Eastern Carpathians frequently include a taxon of the Valeriana tripteris and V. montana affinity, under various names, most frequently as Valeriana transsilvanica or V. tripteris subsp. heterophylla. After having collected and cultivated a new material from Slovakia and Poland, we discovered that the taxon in question is a separate species, a tetraploid (2n=32) occupying a special habitat and a wide geographical range in Poland, Slovakia, Ukraine and Romania, distinct from both V. tripteris and V. montana. An analysis of relevant (seventeen) names and their original material, where applicable, found the name Valeriana dacica Porcius as the correct specific name for this taxon. Diagnostic characters, habitat requirements and an outline of its geographic distribution are provided. Notes on all relevant names, including the misapplied ones or invalid names surviving in important databases are given. Five names are newly typified.